Aberrant canal configuration of the maxillary first molar - Anshuman Kharbanda; Pooja Sood; Rajiv Bali; Haridarshan Sidhu (Wolters Kluwer Medknow Publications, 2015)
Aberrations in the root canal anatomy are a commonly occurring phenomenon. A thorough knowledge of the basic root canal anatomy and its variations is necessary for successful completion of the endodontic treatment. Maxillary first molars usually have three roots and three or four canals (two mesiobuccal canals, one distobuccal and one palatal canal). The incidence of two palatal canals in a palatal root is quite rare. This case provides an evidence of variations in the root canals in palatal root of maxillary first molar. Clinicians should thoroughly examine the pulpal floor and radiographs for the possibility of additional canals. The clinician must know not only the normal root canal anatomy but also variation from the normal. It is also paramount for the clinician to seek out every possible aberration of root canal anatomy for all teeth undergoing treatment.